Electrodeposition of tellurium and cadmium telluride on gold from deep eutectic solvents based on choline chloride - Santos, Luís Paulo Mourão dos (2019)
Te is one of the most important for the production of materials in sectors, such as clean energy, electronics, and defense. On the other hand, over the last decade, tremendous attention has been given to the Deep Eutectic Solvents (DESs) because of their physical and chemical properties, which become these solvents one of the most important agent chemicals to electrodeposition of metals and alloys. Therefore, the main goal of this investigation was the electrodeposition of Te in choline chloride-ethylene glycol and choline chloride-urea based eutectic mixtures, at a molar ration of 1:2, at several temperatures. In both DESs, the electrochemical study revealed two cathodic waves for the Te plating solutions; the first associated with Te4+/Te and the second one to Te/Te2– redox couple on the Au substrate. AFM analyses demonstrated that Te electrocrystalisation on Au electrode proceeded by three-dimensional progressive nucleation mechanism in both eutectic solvents. These results corroborated with predicted by the Scharifker-Hills model. In addition, SEM micrographs of Te electrodeposits from both solvents revealed a large-scale Te rods-like morphology with a hexagonal cross-section in nanoscale regime uniformly distributed on electrode surface. TEM investigation suggested that Te single-crystalline grew perpendicular direction of (100) planes which implied in the preferential growth direction of [001]. Furthermore, the electrodeposition and characterisation of CdTe semiconductor were performed in choline chloride-ethylene glycol-based DES. The electrochemical results have shown that the formation of CdTe occurs at the same region of reduction of Cd2+ to Cd. XRD suggested that CdTe films grew with the crystallite in nanosize regime preferentially oriented along the (111) and (311) planes. SEM examination demonstrated that surface morphology of CdTe coatings exhibited a uniform distribution of spherical-like clusters with large agglomerated crystallite increasing as the temperature goes up. Finally, it was found a blue shift in the optical bandgap of the CdTe films which could be associated with the quantum-confinement effects.